2012
DOI: 10.1001/archdermatol.2011.342
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking in Cutaneous Lupus Erythematosus

Abstract: To investigate cigarette smoking in cutaneous lupus erythematosus (CLE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 21 publications
11
50
0
1
Order By: Relevance
“…Three of the 45 patients in this group were current smokers. Comparing our data with previously published lupus data that found that 50 of 149 patients with active CLE were current smokers, 10 the number of current smokers is significantly less in DM than CLE (P=0.0002).…”
Section: Resultssupporting
confidence: 81%
“…Three of the 45 patients in this group were current smokers. Comparing our data with previously published lupus data that found that 50 of 149 patients with active CLE were current smokers, 10 the number of current smokers is significantly less in DM than CLE (P=0.0002).…”
Section: Resultssupporting
confidence: 81%
“…However, we chose to suspend the treatment due to improvement in the vision of the patient and the report of the ophthalmologist. Moreover, we must not forget that smoking has been linked to a decrease in the efficacy of antimalarial drugs in several studies [20,21], so it is important to advise patients about the need to give up smoking. Considering our case series, we think that a longer duration of antimalarial therapy at a higher dose may be necessary due to the relapse of 5 patients, 2 of whom relapsed after 5 and 6 months of treatment (patients 5 and 7).…”
Section: Discussionmentioning
confidence: 99%
“…Quinacrine users (n=314) were more likely to have smoking history (current=20.6%, past=28.8%, never=50%) than non-users (n=222, current=16.2%, past=19.4%, never=64.4%), χ 2 (2, N =536) =10.79, p=0.0045, likely representing treatment escalations required in smokers (Table 1). 2 …”
Section: To the Editormentioning
confidence: 99%